THE PROBLEM OF AMERICAN BORN CHINESES INTERRACIAL MARRIAGE AS SEEN IN THE JOY LUCK CLUB - May Ariani Susilo; Ekawati Dukut; Liza Dwi Ardhiyanti (Soegijapranata Catholic University, 2004)
One thing that commonly happens in a multiracial country is the interracial marriage, so does in America. As we know that America is a multiracial country, a place where people with different races, ethnic and culture live. Here, many different ethnics start to interact and mix. The interracial marriage usually is not easy. The couple has to face the different cultures problems, besides that they also will face another problem from their families or society, the interracial marriage rejection. In the case of interracial marriage rejection, I will divide the rejection based on its reasons. The first reason is different cultures and the second reason is the generation gap.